Manajemen Program PKL dengan Model Kirkpatrick: Strategi Pengembangan Kompetensi Siswa di Dunia Kerja - Imelia Sahda Salsabilla; Karnadi (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2024)
This study aims to understand the experience experienced by students in participating in the Field Work Practice (PKL) program at SMK Negeri 4 Semarang as part of industry based learning. The method used is phenomenological qualitative, focusing on the interpretation of students' subjective experiences on the process of planning, implementing, and evaluating street vendor programs. Participants consisted of five grade XII students from the departments of Electrical Engineering, Mechanical Engineering, and Design and Animation who are undergoing street vendors in partner industries. Data was collected through interviews, participatory observations, and documentation, then analyzed to uncover the essential meaning of their experiences. The results of the study show that street vendors make a significant contribution to improving technical skills, discipline, responsibility, and adaptation to work culture. In addition, the findings reveal the importance of school support and industry advisors in shaping students' job readiness. The implications of this study confirm the need for a street vendor program management strategy with the Kirkpatrick model evaluation approach to ensure the effectiveness of developing students' competencies and productivity in the world of work. Further research is suggested to expand to various departments and regions to enrich understanding of the dynamics of street vendors in vocational high schools.